Two Communities, or Community of Practice? Communicating Wildlife Rsearch in Northern Botswana - Morrison, Monica (My University, 2021)
Selected research outputs, research permits, management documents, and interviews indicate that Botswana wildlife research stakeholders make up an identifiable community of practice, characterized by mutual engagement, joint enterprise, and shared repertoire. Communication, within this community of practice, and to outside actors, however, should be strengthened, to both inform debate and to allow findings to be put to more use in continuously improving management of wildlife resources.
Keywords: Research uptake; Communities of Practice (CoPs); environmental policy